PENGARUH SOCIAL MEDIA TERHADAP PERILAKU PENCARIAN INFORMASI KESEHATAN PADA REMAJA - Dwi Nur Siti Marchamah; Feiza Rizqita Jayadilaga (Universitas Banten Jaya, 2022)
Technological developments have led to an increase in social media users. Social media is a technology that can search and share information in the form of text, images, audio, video, and location. Information seeking behavior starts from a person's need to obtain information. The type of information that is sought after by the public regarding health. This study aims to determine the effect of social media on health information seeking behavior in adolescents. The study used a correlational analytic study, with a cross sectional research design. The research was conducted at SMK X Semarang City. The population is youth of SMK X Semarang City as many as 227 people. The sampling technique was by means of cluster random sampling as many as 43 people. Collecting data using a questionnaire. Test the validity and reliability test using Cronbach Alpha. Bivariate analysis using Spearman's rho. The results showed that the sig value of 0.000 <0.05 means that there is a significant relationship. The correlation coefficient value of 0.554 means a strong level of influence. So that social media affects the behavior of seeking health information in adolescents, and it often occurs in adolescents as many as 18 people (41.9%).